MINERALOGI MATRIKS BREKSI GUNUNG API PLISTOSEN AKHIR – KUARTER BERDASARKAN DATA XRD DI DAERAH LOMBOK TIMUR, NUSA TENGGARA BARAT - Sigit Maryanto; R. Hasan; Darwin A Siregar (Pusat Survei Geologi, 2009)
Late Pleistocene to Quarternary volcanic rock units of the Kalipalung, Kalibabak, and Lekopiko Formations are well cropped out at East Lombok area, composed predominantly of volcanic breccias. The volcanic breccia of the Kalipalung Formation composed of andesite, porphyry andesite, basaltic andesite, basalt, and altered igneous rocks fragments. The frequence of the occurrence of the andesites and basalts is balanced. The volcanic breccia of the Kalibabak Formation composed predominantly of andesite, porphyry andesite, and rarely basaltic andesite and basalt rock fragments. The volcanic breccia of the Lekopiko Formation composed predominantly of pumice and less of andesite rock fragments, as well as sand and conglomeratic sands. XRD analysis of selected volcanic breccias matrix shows that the plagioclase change from labradorite and andesine on the Kalipalung and Kalibabak Formation to andesine, oligoclase and albite on the Lekopiko Formation. From the old to young formations, the orthopyroxene and clinopyroxene change to orthopyroxene, and finally these minerals was dissapeared. The clay minerals of montmorilonite commomly preserved on the old formation, it dissapeared and replaced by kaolinite in the young formation. Based on the difference test between two means it appears that the Kalipalung and Kalibabak Formations are similar on their mineralogical characters. On the other hand, the Kalipalung Formatian has a real difference on the mineralogical character with the Lekopiko Formation, as well as the Kalibabak Formation with the Lekopiko Formations.Â Keywords: Earth Lombok, breccias matrix, mineralogy